Human and planetary health on fire - Akdis, Cezmi A; Nadeau, Kari C (Nature reviews. Immunology, 2022)
Wildfires are increasing globally, with several recent catastrophic wildfires linked to climate change. Here, we consider the negative impact of the toxic contaminants arising from these fires on the immune system, with a focus on how wildfire pollution can exacerbate inflammatory diseases.